RESEARCH ON AESTHETIC COGNITION, FLOW EXPERIENCE AND TECHNOLOGY ACCEPTANCE IN VIRTUAL CULTURAL ACTIVITIES: Received: 29th March 2024 Revised: 2nd May 2024, 24th May 2024 & 30th May 2024 Accepted: 2nd April 2024 - Hui-Yun Yen (PEOPLE: International Journal of Social Sciences, 2024)
This research delves into integrating aesthetic experience and technology acceptance within virtual cultural activities, with the primary goal of enhancing user engagement. To achieve this, the study employs a meticulously structured questionnaire to assess participants’ aesthetic cognition, flow experience, and acceptance of technology. The methodology involves comprehensive data collection from participants engaged in various virtual cultural events, followed by detailed analytical comparisons to understand user preferences and behaviors. The results clearly indicate a strong preference for immersive and user-friendly technological interfaces. This preference underscores the critical role of aesthetic cognition in determining the success of cultural activities. Furthermore, the findings suggest that significant improvements in interactive features could dramatically enhance user participation and engagement in virtual cultural environments, thereby enriching the overall experience and effectiveness of these activities.